Comparative pharmacokinetics of free doxorubicin and a liposomal formulation in cats following intravenous administration - Liu, Yu; Chen, Sumeng; Wen, Zeyu; Meng, Jinyan; Yang, Yuxin; Zhang, Yang; Wang, Jianzhong; Cao, Xingyuan (Frontiers in Veterinary Science, 2024)
Doxorubicin, a potent chemotherapeutic agent used extensively in cancer treatment, displays complex pharmacokinetic behavior, especially across various formulations. With a rising incidence of cancer cases in cats, understanding the drug's pharmacokinetics in feline subjects remains a critical yet unexplored area. Hence, this study investigated the pharmacokinetic profile of doxorubicin after slow intravenous administration of doxorubicin hydrochloride (DOX•HCl) or doxorubicin hydrochloride pegylated liposome (DOX•HCl-PLI) in twelve cats at a single dose of 20 mg/m 2 . Blood samples collected at pretreatment time (0 hr) and over 192 hours were analyzed using ultra-performance liquid chromatography-mass spectrometry (UPLC-MS/MS).The obtained pharmacokinetic parameters of doxorubicin revealed significant differences between the two formulations and were as follows: elimination half-life (T1/2λz) of 5.00 ± 3.20 hr (DOX•HCl) and 17.62 ± 8.13 hr (DOX•HCl-PLI), area under the concentration/time curve from 0 to last point (AUClast) of 0.67 ± 0.12 µg hr/mL (DOX•HCl) and 783.09 ± 267.29 µg hr/mL (DOX•HCl-PLI), and total body clearance (CL_obs) of 27098.58 ± 5205.19 mL/hr/m 2 (DOX•HCl) and 28.65 ± 11.09 mL/hr/m 2 (DOX•HCl-PLI). Additionally, differences were also detected in the apparent volume of distribution (Vz_obs) with 178.56 ± 71.89 L/m 2 (DOX•HCl) and 0.64 ± 0.20 L/m 2 (DOX•HCl-PLI), and the maximum plasma concentration (Cmax) with 2.25 ±0.30 µg/mL (DOX•HCl) and 24.02 ± 5.45 µg/mL (DOX•HCl-PLI). Notably, low concentration of doxorubicinol, the metabolite of doxorubicin, was detected in plasma after administration of DOX•HCl, with even less present when DOX•HCl-PLI was administered.This investigation provides valuable insights into the distinct pharmacokinetic behaviors of DOX•HCl and DOX•HCl-PLI in cats, contributing essential groundwork for future studies and potential clinical applications in feline oncology.